Perilaku Swamedikasi - Laurensius Amedeo Sitindaon (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2020)
Background: Self-medication is the behavior of consuming the medication itself based on the diagnosis of the symptoms that occur. Self-medication is part of